(untitled) (Latakia University Journal -Engineering Sciences Series, 2018)
تعتبر شبكات الجيل الثالث من أكثر الشبكات انتشارا" اليوم نظرا" للخدمات المميزة التي تقدمها للمستخدم، من أهم مزايا الجيل الثالث من تقنية الاتصالات النقالة هي القدرة على دعم عدد أكبر من مستخدمي الصوت والبيانات في وقت واحد وبمعدلات نقل بيانات سريعة جدا"،ومن أشهر تطبيقات شبكات الجيل الثالث تقنية"UMTS" النظام العالمي للاتصالات المتنقلة التي تؤمن وصول المستخدمين لشبكة الانترنت في أي وقت،ومع النمو المتزايد لتكنولوجيا الانترنت وازدياد عدد المستخدمين كانت التوجهات إلى أي مدى يمكن تحسين هذه التكنولوجيا، فتم إيجاد نظام UMTS الخليوي بالإضافة إلى وجود عدد من التطبيقات التي تعتمد على هذا النظام والتي تتطلب دفق كبير للمعطيات ونقلها بالزمن الحقيقي كالتطبيق الذي قمنا بدراسته وهو نقل الصوت عبر الانترنت VOIP، تأتي أهمية هذا البروتوكول كونه يحل مكان تقنية الـ TDM حيث أنه ينقل رزم الإشارة الصوتية بعد ترميزها عبر الـ IP وكون كلفته منخفضة هذا ما أدى لانتشاره بشكل واسع في شبكات الـUMTS. تقدم تقنية الـ VOIP خدمات الهاتف العادي، بالإضافة إلى خدمات أخرى مثل القدرة على إنشاء محادثة متعددة الأطراف والبريد الصوتي، وإمكانية تخصيص النغمات وإضافة تفاصيل الأشخاص المتصل بهم وحفظها، والقدرة على التحكم في الأرقام مثل منع الاتصال برقم معين أو استقباله، كما تمكن من ارسال واستقبال البيانات مثل الصور والمستندات أثناء إجراء المحادثة الصوتية. يهدف البحث إلى تقييم جودة نقل الصوت VOIP عبر شبكة UMTS خاصة افتراضية مكونة من شبكتين فرعيتين في موقعين مختلفين يبعدان عن بعضهما مسافة قدرها 80 Km، وذلك بدراسة سيناريوهات نقل الصوت باستخدام بروتوكول الإنترنت ضمن شبكة UMTS المستخدمة لنقل البيانات من خلال قياس التأخير والضياع باستخدام برنامج المحاكاة OPNET الذي يوفر بيئة تحاكي تماما" واقع الشبكة المدروسة، وقد مكّنت النتائج التي تم التوصل إليها إضافة إلى تقييم جودة خدمة نقل الصوت من تحديد عرض الحزمة اللازم، ونوع ترميز الصوت الواجب استخدامه. The third generation of network systems is the prevalent today because of special services provided by the user, the most important third-generation advantages of mobile communications technology is the ability to support a greater number of voice users and data at one time and the rate is very fast data transfer, the most famous applications third-generation networks is "UMTS" technology global system for mobile Communications, which provides users access to the internet at anytime and anywhere, as it is with the increasing growth of internet technology and the increasing number of users were trends to what extent can we improve the technology, and was finding UMTS cellular system, plus to the emergence of a number of applications that rely on this system, which requires a large stream of data such as voice transmission over the internet (VOIP) and transfer of data in real time, the importance of this protocol solves the technology being the place where it transports TDMA voice signal packets after coding across the IP and the fact that low cost is what has led to spread widely in the UMTS networks. VOIP technical Provides regular phone services, as well as other services such as the ability to create a multilateral conversation, voice mail, and the ability to customize ringtones and add details of people their caller and saved, was also able to send and receive data such as images and documents during a voice conversation. The research aims to assess the quality of the sound VOIP transmission over a private UMTS virtual network made up of two networks subgroups in two different locations are within about each other a distance of 80 Km, by examining VoIP scenarios using IP within the UMTS network used to transfer data through the delay and loss using simulation OPNET measurement program which It provides an environment perfectly mimic "the reality of the studied network, has enabled the results that have been reached in addition to evaluating the quality of voice transmission determine the width required service package, the type of audio encoding to be used.